EFEKTIVITAS AIR NIRA LONTAR ( Borassusflabellifer) SEBAGAI BAHAN PENGEMBANG ADONAN KUE APEM - Irmayuni, Endang; Nurmila, Nurmila; Sukainah, Andi (Jurnal Pendidikan Teknologi Pertanian, 2018)
This research aim to find out influence fermentation time and amount water concentration niralontar to chemical characteristics and organoleptic test of apemcake . This research is (RAL Factorial ) which consists of from two factor. Factor A with fermentation time niralontar (0 hours, 3 hours and 5 hours) and factor B addition concentration niralontar (100 ml and 200 ml) do with 6 treatments and 3 repetitions . The variables observed is organoleptic test, levels carbohydrates test, pH value test and khamir amount test. The Technique analysis in this research is analysis variance which processed with using SPSS version 22. Research results for value amount khamir the best is fermentation time 5 hours with amount leavened as much 6.58 log colony / ml and for the best pH value is on the fermentation time of 0 hours with pH value of 5.26. While for test organoleptic and levels carbohydrates of treatment fermentation 0 hours with addition concentration niralontar 100 ml ( A1B1) is the best treatment on product apem cake.